IRIS opens pupils' eyes to real space research. Issue 1 (1st February 2019) - Hatfield, Peter; Furnell, W; Shenoy, A; Fox, E; Parker, B; Thomas, L; Rushton, E A C
Abstract : Peter Hatfield and colleagues describe the outcomes of the LUCID project. Abstract: Peter Hatfield and a team of IRIS students and staff describe the outcomes of the LUCID project – a shining example of real research in the classroom.